Inhibitors of dual-specificity tyrosine phosphorylation-regulated kinases (DYRK) exert a strong anti-herpesviral activity - Hutterer, Corina; Milbradt, Jens; Hamilton, Stuart; Zaja, Mirko; Leban, Johann; Henry, Christophe; Vitt, Daniel; Steingruber, Mirjam; Sonntag, Eric; Zeitträger, Isabel; Bahsi, Hanife; Stamminger, Thomas; et al. (Antiviral Research, 2017)
Infection with human cytomegalovirus (HCMV) is a serious medical problem, particularly in immunocompromised individuals and neonates. The success of (val)ganciclovir therapy is hampered by low drug compatibility and induction of viral resistance. A novel strategy of antiviral treatment is based on the exploitation of cell-directed signaling, e. g. pathways with a known relevance for carcinogenesis and tumor drug development. Here we describe a principle for putative antiviral drugs based on targeting dual-specificity tyrosine phosphorylation-regulated kinases (DYRKs). DYRKs constitute an evolutionarily conserved family of protein kinases with key roles in the control of cell proliferation and differentiation. Members of the DYRK family are capable of phosphorylating a number of substrate proteins, including regulators of the cell cycle, e.g. DYRK1B can induce cell cycle arrest, a critical step for the regulation of HCMV replication. Here we provide first evidence for a critical role of DYRKs during viral replication and the high antiviral potential of DYRK inhibitors (SC84227, SC97202 and SC97208, Harmine and AZ-191). Using established replication assays for laboratory and clinically relevant strains of HCMV, concentration-dependent profiles of inhibition were obtained. Mean inhibitory concentrations (EC50) of 0.98 ± 0.08 μM/SC84227, 0.60 ± 0.02 μM/SC97202, 6.26 ± 1.64 μM/SC97208, 0.71 ± 0.019 μM/Harmine and 0.63 ± 0.23 μM/AZ-191 were determined with HCMV strain AD169-GFP for the infection of primary human fibroblasts. A first analysis of the mode of antiviral action suggested a block of viral replication at the early-late stage of HCMV gene expression. Moreover, rhesus macaque cytomegalovirus (RhCMV), varicella-zoster virus (VZV) and herpes simplex virus (HSV-1) showed a similarly high sensitivity to these compounds. Thus, we conclude that DYRK signaling represents a promising target pathway for the development of novel anti-herpesviral strategies.
EVALuna2:33759